RIMPANG JAHE (Zingiberis rhizomae roxb) TERHADAP KADAR PROTEIN IKAN KEMBUNG (Rastrelliger kanagurta) - Evi Diyah Woelansari; Ocky Dwi Suprobowati; Tutik Putri Sri Muljati (Poltekkes Kemenkes Surabaya, 2014)
Rastrelliger kanagurta fish has a lot of edible protein consumed by human. The highcontents of its protein will develop bacteria growth generating damages. One of naturalpreservatives known is Ginger (Zingiber officinale roxb). Moreover, ginger also has a good trait ofantibacterial. The aim of this research is to obtain the effects of ginger rhizome (Zingiberis rhizomae roxb) extract to protein content of Rastrelliger kanagurta fish. The research was conducted atChemistry Laboratory of Laboratorium Terpadu Poltekkes Kemenkes Surabaya. Ginger extractadditional of 0%, 3%, and 6% to the fresh of Rastrelliger kanagurta fish within 10, 20, and 30minutes. Statistic result showed Anova test p 0.074 (0.05) and Posh Hoc test was 0.000 0.01 (0.01). It was concluded that there was no influence of ginger extract additional in the level content protein of fresh Rastrelliger kanagurta fish. Therefore, further research of ginger content throughextraction methods is required, to obtain its effectivity towards bacteria causing damages of fishprotein level. Keyword : Rastrelliger kanagurta fish, Ginger (Zingiber officinale roxb), protein